2013
DOI: 10.1111/jgs.12449
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of an Automated Exercise Coach for Older Adults

Abstract: An automated exercise promotion system deployed from outpatient clinics increased walking among older adults over the short-term. Effective methods for long-term maintenance of behavior change are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
284
2
9

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(329 citation statements)
references
References 47 publications
3
284
2
9
Order By: Relevance
“…Of the 9 studies that used the Internet as the main intervention component, 5 reported significant differences between groups in increasing physical activity. 98,100,102,106,107 The outcomes differed in each study and included increases in step counts, increases in moderately vigorous physical activity, increases in moderate physical activity, and increases in minutes per week of physical activity. Two of the 14 studies examined the use of SMS, 103,109 and both reported significant differences between the intervention and control or comparative conditions.…”
Section: Review Of Evidence For the Efficacy Of Mobile Technologybasementioning
confidence: 99%
See 1 more Smart Citation
“…Of the 9 studies that used the Internet as the main intervention component, 5 reported significant differences between groups in increasing physical activity. 98,100,102,106,107 The outcomes differed in each study and included increases in step counts, increases in moderately vigorous physical activity, increases in moderate physical activity, and increases in minutes per week of physical activity. Two of the 14 studies examined the use of SMS, 103,109 and both reported significant differences between the intervention and control or comparative conditions.…”
Section: Review Of Evidence For the Efficacy Of Mobile Technologybasementioning
confidence: 99%
“…98,97,[100][101][102][103]106,107,109 Overall, the technology that was used most often to increase physical activity was the Internet through Web sites, online tutorials, or networking opportunities. Many of the programs that used the Internet also used other forms of technology, including pedometers and feedback messages via e-mail.…”
Section: Review Of Evidence For the Efficacy Of Mobile Technologybasementioning
confidence: 99%
“…While this approach deserves consideration, other strategies would include, for example, enhancing the clinicians' own ability to deliver effective exercise counseling through education and training in motivational interviewing. Moreover, additional approaches that target and engage patients directly, such as mobile health (e.g., via texting or smartphone applications) and other automated technologies, 5 could be linked to EVS to enhance the capacity of primary care to motivate physical activity.…”
Section: F Ive Decades Ago President Eisenhower Launched Andmentioning
confidence: 99%
“…Bickmore et al (2013) analyzed month-long phases of interactions of older adults with a personified exercise coaching system -it used spoken language, but user input was selected from sets of touchscreen buttons. Sidner et al (2013) addressed the social support aspect, attempting to identify preferred domains of conversation or joint activity based on the same system design.…”
Section: Related Work 21 Assistive and Accompanying Systemsmentioning
confidence: 99%